FEATURES OF INVESTMENT TO THE AGRARIAN SECTOR OF THE CARPATHIAN MACROREGION - Sus, T.Yo. (The actual problems of regional economy development, 2017)
The article analyzes the modern strategy of agrarian sphere development in the Carpathian macro region. It was noted that the orientation of investments to increase the production of grain and oilseeds, the creation of a transport infrastructure for the export of low value added products will not create priorities for investing in environmentally friendly agricultural production and production of products with high added value, in particular in the processing and food industry. In modern conditions, the main task of local authorities in terms of increasing the competitive advantages of agricultural production is to use the land more effectively, the unique opportunities of the macro-region and provide the population with a sufficient quantity of high-quality food products, and the industrial sector-raw materials. The factors that determine the investment attractiveness of the agrarian sphere are considered. For many years, investment priorities have been given to crop production, in particular the cultivation of highly profitable crops: canola, sunflower, cereals and soya. The analysis of attraction of direct foreign investments into the agrarian sphere of the macro-region. The main problems, which hinder large-scale attraction of investments in agrarian sphere of macro-region and need to be solved, are outlined.